Govorne tehnologije - Žganec Gros, Jerneja (Jezik in slovstvo, 2003)
Speech corpora are an essential infrastucture element for speech technologies research in a given language. Speech corpora consist of machine-readable speech recordings. They are futher equipped with additional data, such as speaker and recording session descriptors and different segmentation and annotation elements, e.g. graphemic, phonetic and prosodic transcriptions or descriptors. In the article we describe the process of designing a speech corpus - from text or topic selection, recording, segmentation and labelling procedures. We conclude with an overview of speech corpora for the Slovene language.
Keywords: Slovene; slovenščina; govorne zbirke; govor; govorne tehnologije